Structural and binding properties of laminarin revealed by analytical ultracentrifugation and calorimetric analyses. (5th August 2016) - Oda, Masayuki; Tanabe, Yoichi; Noda, Masanori; Inaba, Satomi; Krayukhina, Elena; Fukada, Harumi; Uchiyama, Susumu
Abstract: One of the β-1, 3-glucans, laminarin, has been widely used as a substrate for enzymes including endo-1, 3-β-glucanase. To obtain quantitative information about the molecular interaction between laminarin and endo-1, 3-β-glucanase, the structural properties of laminarin should be determined. The results from pioneering work using analytical ultracentrifugation for carbohydrate analysis showed that laminarin from Laminaria digitata predominantly exists as a single-chain species with approximately 5% of triple-helical species. Differential scanning calorimetry experiments did not show a peak assignable to the transition from triple-helix to single-chain, supporting the notion that a large proportion of laminarin is the single-chain species. The interaction of laminarin with an inactive variant of endo-1, 3-β-glucanase from Cellulosimicrobium cellulans, E119A, was quantitatively analyzed using isothermal titration calorimetry. The binding was enthalpically driven and the binding affinity was approximately 10 6 M −1 . The results from binding stoichiometric analysis indicated that on average, E119A binds to laminarin in a 2:1 ratio. This seems to be reasonable, because laminarin mainly exists as a monomer, the apparent molecular mass of laminarin is 3.6 kDa, and E119A would have substrate-binding subsites corresponding to 6 glucose units. The analytical ultracentrifugation experiments could detect different complex species of laminarin and endo-1, 3-β-glucanase. Graphical abstract: Highlights: Laminarin mainly exists as a single-chain species. The binding thermodynamics of laminarin to glucanase could be determined. Analytical ultracentrifugation could detect the laminarin binding complex.